DEVELOPING NUMBER AND DATE OF SORGHUM IN THE CONDITION OF SYRDARYA PROVINCE - Ch. V. Toshpulatov; B. B. Tukhtashev; B. T. Mavlonov (Journals Park Publishing, 2025)
It is no secret that the rapid land reclamation, i.e., their salinization and depletion of irrigation water reserves, will turn Uzbekistan into the most difficult region of the arid region in the coming years. Now it is appropriate to conduct large-scale practical and scientific research on improving the land reclamation state of soils and saving irrigation water reserves in the republic's agriculture (4, 5, 10). During the visit of the President of the Republic of Uzbekistan to the Syrdarya region in May 2017 and April 2018, the "Bek Cluster" enterprise was established, where it is planned to grow 80 thousand tons of fodder crops. In order to achieve the specific task set out above, the cultivation of fodder crops in the conditions of the Syrdarya province is an urgent issue